2021
DOI: 10.1021/acssuschemeng.1c04544
|View full text |Cite
|
Sign up to set email alerts
|

Heterostructured VN/Mo2C Nanoparticles as Highly Efficient pH-Universal Electrocatalysts toward the Hydrogen Evolution Reaction

Abstract: Development of cost-effective and high-efficiency electrocatalysts for the hydrogen evolution reaction (HER) is still of great significance for industrial clean hydrogen fuel production. Herein, a novel heterostructured VN/Mo2C nanoparticle is synthesized by a facile and one-step pyrolysis protocol. When applied for the HER, the optimized VN/Mo2C catalyst exhibited quite low overpotentials (alkaline medium: 45 mV, acid medium: 140 mV, and neutral medium: 180 mV) for driving the current density of 10 mA cm–2, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…As illustrated in Figure 4b, the Tafel slope of Ni 3 P/Ni/ VN@NC was 190.9 mV dec À 1 , smaller than those of Ni/VN@NC, Ni 3 P/Ni@NC and Ni@NC with respective Tafel slopes of 206.7, 216.6 and 304.4 mV dec À 1 , indicating that the faster HER reaction kinetics for Ni 3 P/Ni/VN@NC and followed the Volmer-Heyrovsky mechanism. [57][58] Furthermore, the electrochemical impedance spectroscopy (EIS) measurements of the samples were conducted to estimate the charge transfer properties. The Nyquist plots and fitted equivalent circuit diagrams for Ni 3 P/Ni/VN@NC, Ni/VN@NC, Ni 3 P/Ni@NC and Ni@NC were depicted in Figure 4c.…”
Section: Electrocatalytic Her Performance Of the As-synthesized Catal...mentioning
confidence: 99%
“…As illustrated in Figure 4b, the Tafel slope of Ni 3 P/Ni/ VN@NC was 190.9 mV dec À 1 , smaller than those of Ni/VN@NC, Ni 3 P/Ni@NC and Ni@NC with respective Tafel slopes of 206.7, 216.6 and 304.4 mV dec À 1 , indicating that the faster HER reaction kinetics for Ni 3 P/Ni/VN@NC and followed the Volmer-Heyrovsky mechanism. [57][58] Furthermore, the electrochemical impedance spectroscopy (EIS) measurements of the samples were conducted to estimate the charge transfer properties. The Nyquist plots and fitted equivalent circuit diagrams for Ni 3 P/Ni/VN@NC, Ni/VN@NC, Ni 3 P/Ni@NC and Ni@NC were depicted in Figure 4c.…”
Section: Electrocatalytic Her Performance Of the As-synthesized Catal...mentioning
confidence: 99%
“…On the other hand, due to the urgent demands for electrolytic production “green” hydrogen by water splitting, research on efficient and cost-affordable catalysts for the HER and OER has been boosted. Among them, molybdenum (Mo) carbide-based materials with similar d-band electronic structures to Pt have shown high HER activity in acidic or alkaline aqueous solution. The HER activity of β-Mo 2 C nanotube in basic media was even better than that in acidic one, which is superior to that of Pt at high current density. Recently, we prepared a self-standing MoC-Mo 2 C electrode by the electro-carbiding route.…”
Section: Introductionmentioning
confidence: 99%
“…Engineering interfacial regulation can be performed between the two phases of the hybrid. Engineering interface modulation is an effective strategy to tune the electronic structure of catalysts, which can optimize the activity and reaction energy barriers of active sites and promote electrocatalytic water splitting. , Chen et al reported an FeNi LDH/MOF composite with a unique 2D/1D structure. The 2D nanosheets combined with a 1D porous structure can provide abundant active sites and mass transfer channels for electrocatalytic water splitting, enhancing the OER catalytic activity .…”
Section: Introductionmentioning
confidence: 99%